Answer:
Explanation:
The first step is to arrange the equations such that the like terms are on the same column.
The next step is to decide on which variable that you want to eliminate and multiplying both rows by appropriate numbers to obtain new coefficients that are equal and opposite.
The next step is to add the equations and solve for the remaining variable.
The final step is to substitute the value of the known variable into either of the equations and solve for the unknown variable.
To solve
4x + 2y = 5
−4x − 5y = 7
We would add equation 1 to equation 2. It becomes
-3y = 12
y = 12/-3 = - 4
Then substitute y = -4 into the first equation. It becomes
4x + 2 × -4 = 5
4x - 8 = 5
4x = 5 + 8 = 13
x = 13/4 = 3.25